Prevalence of High-Risk Groups for Gastric Carcinoma – A Biopsy Finding - KC, Geetika; KC, Shiva Raj; Gyawali, Purnima (Nepalese Medical Journal, 2018)
Introduction: Gastric carcinoma is leading cause of death world wide including Nepal. The 5 years survival rate of gastric carcinoma (25%) has drastically decreased compared to early gastric cancers (90-90%) hence implying the need for early detection. Atrophic gastritis and intestinal metaplasia are considered as major high-risk factors and is a precancerous lesion along with Helicobacter pylori. This study tries to look at the distribution of atrophy and intestinal metaplasia across age and gender and their occurrence in Helicobacter pylori positive cases. Materials and methods: It is Cross-sectional study of a retrospectively collected data at KIST medical college and GRP poly clinic private limited from April 2008 till March 2018. Total of 10,683 cases were included. The slides were stained with Hematoxilin and Eosin stain and Giemsa stain and evaluated by two pathologists. Statistical analysis was done using SPSS vs 21. Results: Total numbers of cases studied were 10,683 with male to female ratio of 1.04:1. The most common age group of the study was 18-40 years (n=6206; 58.8%). Atrophy was seen in 81 (0.8 %) cases, Intestinal metaplasia in 298 (2.8 %) cases and Helicobacter Pylori was positive in 4459 (42.2%) cases. The incidence of atrophic gastritis was more in H. pylori positive group 54 (0.5%) group where as intestinal metaplasia was more in H. pylori negative 190(1.8%) group. Conclusion: Atrophic gastritis and intestinal metaplasia, high-risk factors for gastric carcinoma, were not the common findings. Atrophic gastritis was seen in 0.8% and intestinal metaplasia was seen in 2.8% of the total study population.